THE ROLE OF ALLERGIC FACTORS IN BRONCHIAL ASTHMA AND STRATEGIES FOR THEIR MANAGEMENT (International journal of medical sciences, 2026)
Bronchial asthma is a chronic inflammatory airway disease characterized by variable airflow obstruction and bronchial hyperresponsiveness. Allergic mechanisms play a central role in the pathogenesis of atopic asthma, which represents a substantial proportion of asthma cases worldwide. Major allergens include house dust mites, pollen, animal dander, and food allergens. Immunoglobulin E (IgE)-mediated hypersensitivity reactions lead to airway inflammation driven by T helper 2 (Th2) lymphocytes, eosinophils, and mast cells. Environmental control strategies, allergen elimination, pharmacotherapy with antihistamines and inhaled glucocorticosteroids (ICS), and preventive interventions are key components of asthma management. This article reviews evidence-based data on allergic triggers in bronchial asthma and discusses contemporary management strategies supported by international clinical guidelines and peer-reviewed research.